Communication and marketing in the age of artificial intelligence - Jaramillo Escobar, Bladimir (Scripta Mundi, 2025)
Communication and marketing are two intrinsically linked disciplines that contribute significantly to the development and success of organizations, whether business, educational, social, or political. Historically, marketing has relied on communication to convey persuasive messages to mass audiences. The integration of communication and marketing continues to evolve, even more so in this new digital age, and the emergence of artificial intelligence (AI) has drastically redefined this relationship, introducing new tools, challenges, and opportunities. In the age of AI, communication becomes an even more strategic pillar for marketing, enabling unprecedented personalization, efficient automation, and a deeper understanding of the consumer. Given the rapid development of new technologies, today we talk about digital communication and marketing. With the advent of AI, this dynamic has evolved from a one-way approach to a highly interactive and adaptive one. In this edition, we present eight research articles: three related to communication, two to marketing, and three related to our thematic areas: graphic design, entrepreneurship, and Educommunication.